Tingkat Kepuasan Konsumen Di Restoran Bakso Campur Surabaya Di Bahu Mall Kota Manado - Budiman, Velicia Pingkan; Benu, Noortje Marsellanie; Mandei, Juliana Ruth (AGRI-SOSIOEKONOMI, 2024)
This study aims to analyze the level of consumer satisfaction at Bakso Campur Surabaya in terms of product, price, promotion, location, and service. The study was conducted from August to October 2023. The selection of respondents was done by accident. The data used are primary data and secondary data. Primary data is obtained through direct observation in the field to make observations and conduct interviews with managers and consumers, as well as provide questionnaires to consumers to fill out. Secondary data were obtained from other information data related to this study. Secondary data obtained by researchers from internet sites, books, articles, research journals and various other documents related to research. The results showed that the results of the consumer satisfaction index of Bakso Campur Surabaya at Bahu Mall Manado City in terms of products, prices, locations, promotions and service quality were at 74.20%. This shows that overall the management of Bakso Campur Surabaya at Bahu Mall Manado City has achieved a level of consumer satisfaction although there are still several indicators that need attention.